PENGARUH KEMAMPUAN TEKNIK PEMAKAI SIA, PARTISIPASI MANAJEMEN, INSENTIF, FAKTOR DEMOGRAFI PADA KINERJA INDIVIDU - Dewi, Ni Made Utari Sintia; Suardikha, I Made Sadha (E-Jurnal Akuntansi; Vol 13 No 2 (2015), 2015)
This study aimed to determine the impact of the ability of users of accounting information systems engineering, management participation, incentives and demographic factors on the performance of the individual. This research was conducted at the LPD in the city of Denpasar. Sampling technique used was simple random sampling, resulting in 67 samples can employees. Data were analyzed using multiple linear regression analysis. Data is collected using a questionnaire. The results show the ability of users of accounting information systems engineering, management participation, incentives, gender factor, factor experience positive and significant impact on the performance of the individual. While the age factor shows that the age old and young employees do not significantly affect the performance of the individual, and the high and low education has no effect on the performance of individual.
Keywords: individual performance, the ability of users SIA engineering, management participation, incentives, demographic factors